VALUE RELEVANCE DARI INTANGIBLE ASSETS BAGI USER DI CAPITAL MARKET (Suatu Tinjauan Literatur) - Muliawati . (Center for Economic Studies Universitas Katolik Parahyangan, 2014)
Capital market facilitate buying and selling long term securities. There are many parties involved in capital markets include investors, issuers (companies) and regulators. Agency problems arises when there are conflict of interest between the needs of principals (investors) and agents (companies or issuers). This problem is caused by information asymmetry. Financial statements are principal means through which a company communicate its financial information to interested parties. Financial statements have some limitations. Many items (i.e.intangible assets) that have financial value but cannot realibly measure, omitted from financial statements. Therefore, companies need to disclose more information, either financial or non financial informations to investors. Many investors realize that the importance of intangible assets information. There is value relevance of intangible assets such increase in stock market prices, market capitalization or create value for the company.